2004
DOI: 10.1128/cdli.11.1.227-228.2004
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Antibodies to the Nucleocapsid Protein of the Severe Acute Respiratory Syndrome (SARS)-Associated Coronavirus in Probable SARS Patients

Abstract: Profiles of antibodies to the nucleocapsid protein of the severe acute respiratory syndrome (SARS)-associated coronavirus in 445 probable SARS patients and 3,749 healthy people or non-SARS patients were analyzed by antigen-capturing enzyme-linked immunosorbent assay. Antinucleocapsid antibodies were elucidated in 17.5% of the probable SARS patients 1 to 7 days after the onset of symptoms and in 80% of the patients 8 to 14 days after the onset. About 90% of the probable SARS patients were positive 15 or more da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
56
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 6 publications
5
56
1
Order By: Relevance
“…Since the specific antibodies to nucleocapsid (N) protein are most abundant in the sera from SARS patients (5), several groups have developed some recombinant N protein-based ELISAs. In general, these new assays are more specific and sensitive than the ELISA based on whole-virus lysate, but some false-positive results still occurred with sera from non-SARS patients or healthy people, even with sera collected several years before the SARS outbreak (3,7,8,(10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the specific antibodies to nucleocapsid (N) protein are most abundant in the sera from SARS patients (5), several groups have developed some recombinant N protein-based ELISAs. In general, these new assays are more specific and sensitive than the ELISA based on whole-virus lysate, but some false-positive results still occurred with sera from non-SARS patients or healthy people, even with sera collected several years before the SARS outbreak (3,7,8,(10)(11)(12).…”
mentioning
confidence: 99%
“…Since the specific antibodies to nucleocapsid (N) protein are most abundant in the sera from SARS patients (5), several groups have developed some recombinant N protein-based ELISAs. In general, these new assays are more specific and sensitive than the ELISA based on whole-virus lysate, but some false-positive results still occurred with sera from non-SARS patients or healthy people, even with sera collected several years before the SARS outbreak (3,7,8,(10)(11)(12).Since the N proteins of the known coronaviruses are relatively conserved, the expressed N protein of the SARS-CoV in Escherichia coli cross-reacts with polyclonal antisera of some known animal coronaviruses in antigenic group I, including transmissible gastroenteritis virus, feline infectious peritonitis virus, and canine coronavirus (9), which raised concerns of potential false positives when the recombinant N protein of the SARS-CoV, whole-virus antigen extracts, or virus-infected cells are used as reagents. However, this concern is very minimal, since the two known human coronaviruses (strains 229E and OC43) do not cause severe clinical diseases and we still do not have data about the prevalence of the antibodies to other coronaviruses or relevant microorganisms in human populations (4,6,8).…”
mentioning
confidence: 99%
“…Although very few serum specimens from unexposed persons (Ͻ1.5%) tested positive for SARS-CoV infection, the potential for cross-reactivity between SARSCoV and other coronaviruses, including the known human coronaviruses HCoV-OC43, HCoV-229E, and recently identified HKU1 and NL63, remains a concern (12,13,22). Whether these positive results are due to nonspecific reactivity to the recombinant SARS N protein or to cross-reactivity to other human CoVs requires further study.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the utility of anti-N and anti-S proteins in the diagnosis of SARS-CoV infections (2,5,12,21). In this study, we describe the evaluation and comparison of recombinant spike and nucleocapsid enzyme-linked immunosorbent assays (ELISAs) for specifically detecting SARS-CoV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation